Full-scale experimental and numerical analyses of a flexible riser under combined tension-bending loading. (November 2022) - Lu, Hailong; Vaz, Murilo Augusto; Caire, Marcelo; Hernández, Irving David
Abstract: The flexible riser top connection with floating production units presents additional tensile armour integrity assessment uncertainties associated to the bend stiffener contact interaction that leads to a non-uniform curvature and contact pressure distribution in a region of large dynamic forces and moments. In this paper, a full-scale 6″ flexible riser and bend stiffener bending-tension experimental campaign is carried out in a horizontal rig. The external tensile armour wires are instrumented with strain gauges for axial strain measurement in several riser cross-sections inside and outside the bend stiffener region. The rig assembly allows the riser rotation in order to measure strains at different circumferential angular positions. The bend stiffener polyurethane hyperelastic mechanical response is obtained by uniaxial tensile tests performed at room temperature. A nonlinear finite element model (FEM), including the riser/bend stiffener contact interaction and interlayer friction mechanisms, is employed to numerically investigate the mechanical behaviour of the flexible riser subjected to the experimental loading conditions. The FEM axial strains on the tensile armour wires are compared with the measured results for pure tension and tension-bending loads. Under axisymmetric loading a relevant experimental axial strain dispersion is observed when compared to the average values. Under tension-bending loading, the interlayer friction coefficient influences on the contact pressure and curvature distribution are initially assessed with the numerical model. The strain gauges located in the cross-sections with highest values of contact pressure and curvature are selected for a detailed numerical-experimental strains comparison. In addition, a parametric study is conducted to calibrate the friction coefficient that yields the minimum mean squared error for all measured data. Generally, good correlations are found between the experimental and numerical results. Highlights: Full-scale 6″ flexible riser and bend stiffener bending-tension experimental campaign is carried out. Relevant experimental axial strain dispersion is observed. Nonlinear finite element model, including riser/bend stiffener contact and interlayer friction mechanisms, is developed. A parametric study is conducted to calibrate the friction coefficient that yields the minimum mean squared error. Generally, good correlations are found between the experimental and numerical results.